Temporal patterns of late bowel and bladder radiotherapy toxicity in a randomised controlled trial assessing duration of neo-adjuvant hormones in prostate cancer. (October 2014) - Barry, Aisling S.; Dunne, Mary T.; Lyons, Ciara A.; Finn, Marie A.; Moulton, Brian; Taylor, Judy C.; O'Shea, Carmel M.; Thirion, Pierre G.; Armstrong, John G.
Abstract Background. To assess the temporal patterns of late gastrointestinal (GI) and genitourinary (GU) radiotherapy toxicity and resolution rates in a randomised controlled trial (All-Ireland Cooperative Oncology Research Group 97-01) assessing duration of neo-adjuvant (NA) hormone therapy for localised prostate cancer. Material and methods. Node negative patients with > 1 of: PSA > 20 ng/mL, Gleason score ≥ 7, and stage T3 or more, were included. Follow-up, including toxicity assessment, was three-monthly in the early stages and yearly thereafter. Results. Median follow-up from the end of RT was 6.8 years. In the interval between 90 days following the end of RT and the last toxicity assessment, GI and GU toxicity (any grade) was found in 50% and 51% of 240 and 241 patients, respectively. For those who did develop toxicity, the median time from end of RT until the first development of any grade GI or GU toxicity was 1.2 years and 1.6 years, respectively, whilst median time to final resolution was 1.6 years and 2.2 years, respectively. Grade 2 (G2) or greater GI and GU toxicity occurred in 29 (12.1%) and 40 (16.6%) patients, respectively. The proportion with unresolved G2 + GI and GU toxicity was 89% and 79%, respectively, in year 1, 69% and 65% in year 2, 59% and 52% in year 3 and 27% and 32% in year 5. Conclusion. Long-term toxicities continue to occur many years after NA hormone therapy and RT. The rate of occurrence does not appear to reduce within the time frame during which our patients were followed. The percentage of patients suffering from G2 + toxicity at any time is however low. Resolution of these toxicities continues for the duration of the follow-up.